Answers

2015-06-08T20:01:34+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Sum of -3/4 and -5/12 = (-3/4) + (-5/12)
                                = -3/4-5/12
                                = (-9-5)/12
                                = -14/12
                                = -7/6
product of -3/4 and -5/12 = (-3/4)(-5/12)
                                     = 5/16
Now, (-7/6)/(5/16) = -56/15 .
 

1 5 1
oye lohi okasari last step choodu
sum place lo -7/6 badulu 16 vesav
oh than q akka edit chesthanu aagu
gd
hmm tq
  • Brainly User
2015-06-08T20:17:12+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Firstly we have to add -3/4 and -5/12..................
=  -3/4 + -5/12
= now find the common denominator/Take the L.C.M of denominators

=L.C.M will be 12

=Now we have common denominator 12

= Common Denominator ÷ Denominator) x Numerator = New Numerator

= 1st fraction

= (12 ÷ 4) × -3 = -9

=-9/12

2nd Fraction

=(12 ÷ 12) × -5 = -5

= -5/12

= now add both fractions

=-9 + -5 = -14
   12   12    12

now multiplication

=-3     ×     -5     =     15  
   4            12            48

=now division

=-14/12  /  15/48 

=15 → 48           here we've do the reciprocal
  48    15

=then we have to multiply

= -14 × 48 = -672
    12   15     180

answer will be   -672
                       180




0